Development of a measure to examine nurses' attitudes towards the presence of paid carers who provide care to older patients in hospitals. (February 2014) - Iecovich, Esther
Many older adults who are hospitalised are functionally disabled and/or are cognitively impaired and need help with basic activities. The nursing staff are overloaded with work and families are not always available to look after their hospitalised older family members. Therefore, a growing number of older patients hire paid carers of whom many are migrant live-in care workers who provide them with care at home and in hospitals during hospitalisation. The study was aimed to develop a measure that will examine nursing staff's attitudes towards these paid carers in hospital wards. The measure that was developed includes two dimensions: negative and positive attitudes. The study was conducted in 10 internal medicine and 4 geriatric wards in two general hospitals in Israel. Participants included 265 nurses. Factor analysis loaded two factors that resembled the two dimensions. The final version of the measure included six positive and six negative items, showed good convergent and divergent validity, and good internal consistency for each of the dimensions. Further studies are needed to examine the measure's validity and reliability in different cultural and social contexts.